Lenka J. Budilová – Marek Jakoubek: Bulgarian Protestants and the Czech Village of Voyvodovo: New Bulgarian University, Sofia 2017, 144s. - Dimitrov, Vasil (Lidé města, 2024)
A review of the book by Lenka J. Budilová and Marek Jakoubek.